2018
DOI: 10.1161/circheartfailure.117.004408
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Assessment of Vascular Function With Sunitinib in Patients With Metastatic Renal Cell Carcinoma

Abstract: In patients with metastatic renal cell carcinoma, sunitinib resulted in early, significant increases in blood pressure, arterial stiffness, and resistive and pulsatile load within 3.5 weeks of treatment. Baseline vascular function parameters were associated with worsening diastolic but not systolic function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
23
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 47 publications
6
23
1
1
Order By: Relevance
“…In this study renin and aldosterone levels did not change after sorafenib initiation; however, vascular stiffness did increase. These results were confirmed by Catino et al ( 35 ), who demonstrated increases in arterial stiffness, resistance, and pulsatile load in the setting of sunitinib use. Although the absence of an increase in renin and aldosterone may indicate that the RAAS system is not involved in VEGFi-mediated hypertension, this finding may not fully eliminate the possibility of a relative imbalance between VEGF and RAAS such that the absence of a compensatory decrease in renin and aldosterone after VEGFi administration could possibly play a role in VEGFi-mediated hypertension.…”
Section: Discussionsupporting
confidence: 70%
“…In this study renin and aldosterone levels did not change after sorafenib initiation; however, vascular stiffness did increase. These results were confirmed by Catino et al ( 35 ), who demonstrated increases in arterial stiffness, resistance, and pulsatile load in the setting of sunitinib use. Although the absence of an increase in renin and aldosterone may indicate that the RAAS system is not involved in VEGFi-mediated hypertension, this finding may not fully eliminate the possibility of a relative imbalance between VEGF and RAAS such that the absence of a compensatory decrease in renin and aldosterone after VEGFi administration could possibly play a role in VEGFi-mediated hypertension.…”
Section: Discussionsupporting
confidence: 70%
“…A study in 84 patients with metastatic RCC demonstrated that sunitinib increased large artery stiffness within the first weeks of therapy, as measured by increased carotid-femoral pulse wave velocity. 124 This increase in vascular stiffness was also observed after 3 weeks of sorafenib treatment in another clinical study. 125 Nonetheless, the exact contribution of vascular stiffness to the prohypertensive effects of VEGFI remains unclear, as it could both be a cause and consequence of hypertension.…”
Section: Anticancer Therapy and Hypertensionsupporting
confidence: 53%
“…139 Dihydropyridine calcium channel blockers, such as nifedipine and amlodipine, are direct vasodilators and may be very useful in complex BP control of these patients, although they are negative inotropes. 140 However, the non-dihydropyridine calcium channel blockers (diltiazem and verapamil) are typically contraindicated, since they are inducers of cytochrome P450 3A4 (CYP3A4) resulting in increased VEGF inhibitor drug levels. 141 Factors that can contribute to BP elevation need to be addressed, such as obstructive sleep apnoea, excessive alcohol consumption, nonsteroidal anti-inflammatory drugs, adrenal steroid hormones, erythropoietin, oral contraceptive hormones and sympathomimetics, such as methylphenidate.…”
Section: Annals Of Oncologymentioning
confidence: 99%